2011
DOI: 10.1007/s00442-010-1887-7
|View full text |Cite
|
Sign up to set email alerts
|

Spartina alterniflora invasion increases soil inorganic nitrogen pools through interactions with tidal subsidies in the Yangtze Estuary, China

Abstract: Invasive alien plants increase both plant N and soil inorganic N pools in many terrestrial ecosystems. This is believed to be the result of altered plant-soil-microbe feedbacks that accelerate N cycling. However, it may also be due to the greater ability of invasive species to uptake lateral N subsidies that can modify ecosystem N dynamics. We conducted manipulative field experiments to determine the impact of smooth cordgrass (Spartina alterniflora) invasion on the N cycling of salt marsh ecosystems in the Ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 53 publications
0
48
1
Order By: Relevance
“…6 Regression analyses of soil CO 2 emissions with soil moisture (a), Eh (b), salinity (c) and sulfate (d), within a semi-lunar tidal cycle Wetlands Ecol Manage was absorbed and utilized by plants because the wetland had high plant productivity, especially in S. alterniflora stands (Liao et al 2007). The content of soil sulfate in our study was more than ten times higher than the nitrate content reported in Peng et al (2011), so nitrate may not be a major inhibitor of methanogenesis. Several studies have demonstrated that high soil salinity and sulfate were the most important inhibitors of CH 4 production in coastal wetlands Purvaja and Ramesh 2001;Poffenbarger et al 2011).…”
Section: Tidal Effects On Co 2 and Ch 4 Emissionscontrasting
confidence: 69%
See 1 more Smart Citation
“…6 Regression analyses of soil CO 2 emissions with soil moisture (a), Eh (b), salinity (c) and sulfate (d), within a semi-lunar tidal cycle Wetlands Ecol Manage was absorbed and utilized by plants because the wetland had high plant productivity, especially in S. alterniflora stands (Liao et al 2007). The content of soil sulfate in our study was more than ten times higher than the nitrate content reported in Peng et al (2011), so nitrate may not be a major inhibitor of methanogenesis. Several studies have demonstrated that high soil salinity and sulfate were the most important inhibitors of CH 4 production in coastal wetlands Purvaja and Ramesh 2001;Poffenbarger et al 2011).…”
Section: Tidal Effects On Co 2 and Ch 4 Emissionscontrasting
confidence: 69%
“…on CH 4 production were insignificant or nonexistent in STP. Peng et al (2011) reported that tides imported inorganic nitrogen including nitrate to wetlands of the Yangtze River estuary. However, most inorganic nitrogen y = 11.50 -0.07x R 2 = 0.11, P = 0.01 y = 5.45 + 0.02x R 2 = 0.37, P < 0.0001 y = -9.05x + 14.87 R 2 = 0.24, P < 0.001 y = 12.92 -7.32x R 2 = 0.33, P < 0.0001 Fig.…”
Section: Tidal Effects On Co 2 and Ch 4 Emissionsmentioning
confidence: 98%
“…By examining the impacts of seven widespread invasive plant species in northern Europe, Dassonville et al (2008) observed that invasive species reduced soil K availability in K-rich soils, but increased soil K availability in K-poor soils. The success of alien plants thus appears to depend on high K availability in productive environments and on low K availability in less productive environments; however, the small number of studies precludes formulation of a definitive conclusion about this dependence (Funk & Vitousek, 2007;Peng et al, 2011;. Alien plants with a more efficient use of K may be able to increase their spread in arid areas.…”
Section: K and The Success Of Plant Invasionmentioning
confidence: 99%
“…2). Alien invasion in nutrient-rich environments also frequently favors plant species with high rates of photosynthesis and growth (Baruch and Goldstein, 1999;Leishman et al, 2007;Feng et al, 2008;Schumacher et al, 2009;GonzĂĄlez et al, 2010;Mozdzer and Zieman, 2010;Feng et al, 2011), high reproductive outputs (GonzĂĄlez et al, 2010), large size (van Kleunen et al, 2010), low C-nutrient ratios in tissues (Monaco et al, 2003;Agrawal et al, 2005;Reed et al, 2005;Packett and Chambers, 2006;Schumacher et al, 2009;GonzĂĄlez et al, 2010;Peñuelas et al, 2010), low costs of foliar construction (Nagel and Griffin, 2001;Feng et al, 2007;GonzĂĄlez et al, 2010), large investments of N in photosynthetic production (Ehrenfeld, 2003;Xu et al, 2007;Shen et al, 2011), higher capacities of nutrient uptake (Zabinsky et al, 2002;Harrington et al, 2004;Blank and Sforza, 2007;Feng, 2008;Blank, 2010;Hewins and Hyatt, 2010;Leffler et al, 2011;Peng et al, 2011), and high levels of plasticity in the acquisition of resources as a function of pulses in nutrient availability (Leffler et al, 2011). These factors indicate that nutrient uptake and all foliar traits enabling rapid rates of growth (Zabinsky et al, 2002;Leishman et al, 2007) will help invading species to succeed when resources are not limited (Bray et al, 2003;Shah et al, 2009).…”
Section: Species Invasion the Role Of Soil Nutrients In Alien Successmentioning
confidence: 99%